Aksesoris Siger Pengantin Sunda dari Lem Bakar - Nina Safana Abnajapa; Kuswidyaningrum N. J.; Nurulisma Saputri (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
The expensive Siger accessories make beginner MUAs or beauty students spend money on renting Siger accessories during practice. Therefore, the author is looking for alternative methods to produce cheaper accessories with maximum results. The goal is to understand the production process, assess the feasibility level, and determine the level of public preference for Siger Wedding accessories from hot glue. A descriptive quantitative research method is used, including methods such as observation, literature review, experiments, documentation, and questionnaires. The production process includes several stages: making the frame, creating patterns, and coloring, which uses two experiments with aerosol paint and decorative paint. The product feasibility was assessed by 5 expert validators. Product A received a score of 119, while product B scored 115, indicating that product A is more viable. Additionally, results from a questionnaire completed by 30 respondents show that public preference for the accessories is very high.